A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera: Corydalidae) from India - Liu, Xingyue; Hayashi, Fumio (Zootaxa, 2019)
Neochauliodes van der Weele is the most species-rich genus of Chauliodinae (Megaloptera: Corydalidae). However, to date there are only five species of Neochauliodes recorded from India. Herein, we report a new species of Neochauliodes, N. flinti sp. nov., from northeastern India. An updated key to the species of Neochauliodes from India and adjacent regions of South Asia is also given.